Optimizing Healthcare Access: An Advanced Analytics Solution for Provider Distribution Management - Venkata Prasanna Kumar Pentakota (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The growing complexity of healthcare provider distribution and patient access necessitates sophisticated analytics tools for optimizing physician coverage across geographical regions. This article presents a novel data-driven approach that leverages real-time search patterns from physician finder tools to analyze and visualize provider demand-supply gaps. The proposed system implements a dynamic classification methodology that categorizes geographic areas into red, yellow, and green zones based on the correlation between patient search volumes and existing provider availability. By incorporating multiple variables including specialization density, geographic accessibility, and temporal search patterns, the system provides healthcare organizations with actionable insights for strategic provider recruitment and resource allocation. Initial implementations demonstrate significant improvements in provider coverage optimization and patient access to care. This article suggests that data-driven geographic analysis tools can substantially enhance healthcare organization's ability to proactively address provider shortages and optimize healthcare resource distribution. This article contributes to the growing field of healthcare analytics by providing a scalable framework for data-driven provider distribution decisions.
Keywords: Healthcare Analytics; Geographic Resource Optimization; Provider Distribution; Patient Access Metrics; Demand-Supply Mapping